1990
DOI: 10.1111/j.1600-051x.1990.tb02341.x
|View full text |Cite
|
Sign up to set email alerts
|

Clinical, microbiological and immunological studies on recurrent periodontal disease

Abstract: . The present study was performed to evaluate the clinical, microbiological and immunological aspects in the early stages of recurrent periodontal disease. After clinical monitoring of pockets with recent evidence of disease recurrence, microbiological samples for cultural analysis, serum and gingival crevicular fluid (GCF) samples were taken for IgG antibody analysis from 14 sites, 7 in 6 recurrent periodontitis patients and 7 in 7 periodontally healthy control subjects. IgG responses of serum antibody to 8 g… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
3
1

Citation Types

1
25
0
1

Year Published

1991
1991
2020
2020

Publication Types

Select...
9
1

Relationship

0
10

Authors

Journals

citations
Cited by 51 publications
(27 citation statements)
references
References 56 publications
(26 reference statements)
1
25
0
1
Order By: Relevance
“…A shift in the microbial community leading to outgrowth of this anaerobe is directly linked to periodontitis, a chronic inflammatory disease that leads to destruction of the tissues supporting the gums and ultimately, exfoliation of the teeth (Choil et al, 1990;Dzink et al, 1988;Grossi et al, 1994;Lamont & Jenkinson, 2000;Moore et al, 1991). This commensal can colonize, invade and multiply within gingival epithelial cells, as well as penetrate into deeper epithelial cell layers, potentially releasing the whole organism and/or virulence factors into the bloodstream (reviewed by Yilmaz, 2008).…”
Section: Introductionmentioning
confidence: 99%
“…A shift in the microbial community leading to outgrowth of this anaerobe is directly linked to periodontitis, a chronic inflammatory disease that leads to destruction of the tissues supporting the gums and ultimately, exfoliation of the teeth (Choil et al, 1990;Dzink et al, 1988;Grossi et al, 1994;Lamont & Jenkinson, 2000;Moore et al, 1991). This commensal can colonize, invade and multiply within gingival epithelial cells, as well as penetrate into deeper epithelial cell layers, potentially releasing the whole organism and/or virulence factors into the bloodstream (reviewed by Yilmaz, 2008).…”
Section: Introductionmentioning
confidence: 99%
“…P. gingivalis is a Gram-negative anaerobe that persists within the oral biofilm community. Outgrowth of this normally commensal organism is associated with severe periodontal disease, resulting in the destruction of tissues that support the gums and, ultimately, tooth loss (Choi et al, 1990;Dzink et al, 1988; Grossi et al, 1994;Lamont & Yilmaz, 2002;Moore et al, 1991). Several studies have shown that P. gingivalis can invade and multiply within gingival epithelial cells, as well as penetrate deeper epithelial cell layers, releasing the whole organism and/or virulence factors into the bloodstream (reviewed by Yilmaz, 2008).…”
Section: Introductionmentioning
confidence: 99%
“…Formation of a periodontal pocket, destruction of supporting connective tissues, and loss of alveolar bone take place in the progression of this disease. Although the bacterium may be eliminated by successful therapies [9], it causes recurrent infections [5]. P. gingivalis cells are found in healthy sites [4], but significantly elevated levels of the organism are observed in periodontal lesions [5,6].…”
Section: Introductionmentioning
confidence: 99%